2009
DOI: 10.1080/15622970802256180
|View full text |Cite
|
Sign up to set email alerts
|

Survey of referrals to electroconvulsive therapy in Hungary

Abstract: Considering the very high Hungarian suicide rate, the low referral rate in cases of severe suicidal intent and threat is surprising. The respondents also rarely considered ECT for NMS or severe depression. The discrepancy between current referral practices and standard recommendations could be decreased with more ECT training courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Hence the question arises whether they are open to ECT as a valid treatment option and whether they have enough knowledge to advise their patients adequately. In other countries, the lack of experience of psychiatrists dealing with ECT also has been bemoaned (Yuzda et al 2002;Gazdag et al 2009b;Dinwiddie and Spitz 2010). Specialist training and continuing education for referring physicians appears to us to be a central point for a better patient access to ECT treatment.…”
Section: Remarkable Single Resultsmentioning
confidence: 99%
“…Hence the question arises whether they are open to ECT as a valid treatment option and whether they have enough knowledge to advise their patients adequately. In other countries, the lack of experience of psychiatrists dealing with ECT also has been bemoaned (Yuzda et al 2002;Gazdag et al 2009b;Dinwiddie and Spitz 2010). Specialist training and continuing education for referring physicians appears to us to be a central point for a better patient access to ECT treatment.…”
Section: Remarkable Single Resultsmentioning
confidence: 99%
“…The criteria for ECT prescription are not consistent in the current literature; however, different treatment guidelines propose its indication in patients with schizophrenia with catatonia symptoms, as additional support for pharmacotherapy when there is resistance to treatment, and in patients with a prior positive response to ECT [136,141,142]. It has been reported that treatment resistance is the most common condition in which ECT is prescribed [143]. Furthermore, the symptomatic and cognitive response has been higher when bifrontal electrodes are used [144].…”
Section: Schizophreniamentioning
confidence: 99%
“…A survey of referrals to ECT in Hungary reports that treatment resistance is the most common indication, followed by catatonic symptoms, and a past history of good response to ECT. [ 10 ] A recent Cochrane review reports that ECT can be considered for patients when rapid improvement is desired and when there is a history of poor response to medication alone. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the practice of ECT in teaching hospitals in India, as well as in Asia, reports that schizophrenia (36.5% and 41.8% subsequently) is the most common diagnosis for which patients receive ECT. [ 10 11 ] Therefore, the lingering questions remain as to why schizophrenia patients receive ECT in our country? We have made an attempt to study this in an academic Psychiatric setting in India.…”
Section: Introductionmentioning
confidence: 99%